Identification of a Novel Polyamine Scaffold With Potent Efflux Pump Inhibition Activity Toward Multi-Drug Resistant Bacterial Pathogens - Fleeman, Renee M.; Debevec, Ginamarie; Antonen, Kirsten; Adams, Jessie L.; Santos, Radleigh G.; Welmaker, Gregory S.; Houghten, Richard A.; Giulianotti, Marc A.; Shaw, Lindsey N. (Frontiers in Microbiology, 2018)
We have previously reported the use of combinatorial chemistry to identify broad-spectrum antibacterial agents. Herein, we extend our analysis of this technology toward the discovery of anti-resistance molecules, focusing on efflux pump inhibitors. Using high-throughput screening against multi-drug resistant Pseudomonas aeruginosa, we identified a polyamine scaffold that demonstrated strong efflux pump inhibition without possessing antibacterial effects. We determined that these molecules were most effective with an amine functionality at R1 and benzene functionalities at R2 and R3. From a library of 188 compounds, we studied the properties of 5 lead agents in detail, observing a fivefold to eightfold decrease in the 90% effective concentration of tetracycline, chloramphenicol, and aztreonam toward P. aeruginosa isolates. Additionally, we determined that our molecules were not only active toward P. aeruginosa, but toward Acinetobacter baumannii and Staphylococcus aureus as well. The specificity of our molecules to efflux pump inhibition was confirmed using ethidium bromide accumulation assays, and in studies with strains that displayed varying abilities in their efflux potential. When assessing off target effects we observed no disruption of bacterial membrane polarity, no general toxicity toward mammalian cells, and no inhibition of calcium channel activity in human kidney cells. Finally, combination treatment with our lead agents engendered a marked increase in the bactericidal capacity of tetracycline, and significantly decreased viability within P. aeruginosa biofilms. As such, we report a unique polyamine scaffold that has strong potential for the future development of novel and broadly active efflux pump inhibitors targeting multi-drug resistant bacterial infections.